Reconstruction of Islamic Religious Education Curriculum Responsive to Modern Developments: Analysis of 21st Century Needs - Karisma Ayu Candra (LP3M Pascasarjana STAI Ibnurusyd, 2025)
The 21st-century developments, marked by advances in digital technology, globalization, and social and cultural change, require the world of education to continuously adapt its curriculum. As an integral part of the education system, Islamic Religious Education (PAI) plays a strategic role in shaping the character, morals, and spirituality of students, enabling them to face modern challenges critically and ethically. However, various studies indicate that the PAI curriculum in many educational institutions still tends to be normative, textual, and oriented towards mastery of material, making it less responsive to the dynamics of 21st-century life. Empirical findings reveal that PAI learning has not fully integrated 21st-century skills, such as critical thinking, creativity, collaboration, communication, and digital literacy. As a result, PAI often lacks relevance in addressing contemporary issues, including pluralism, digital ethics challenges, and the crisis of values ​​among the younger generation. Conversely, studies examining innovations in the PAI curriculum indicate that curriculum reconstruction that integrates a contextual approach, the use of technology, and the strengthening of religious moderation values ​​can improve religious understanding, tolerance, and active student engagement in learning. Given these conditions, the reconstruction of the Islamic Religious Education curriculum to be responsive to modern developments is an urgent need. This effort aims to ensure that the Islamic Religious Education curriculum remains relevant, adaptive, and able to meet the needs of 21st-century education without abandoning the substance of Islamic values.